Morphological Index of Sassone for Predicting Serous Type of Epithelial Ovarium Cancer: Indeks Morfologi Sassone untuk Memprediksi Kanker Ovarium Epitelial Tipe Serous - Rachmad Rachmad; Mohd Andalas; Cut M. Yeni; Nurhayani D. Susanti; Reno K. Kamarlis (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objective: To obtain whether there was a correlation between the Sassone morphological index and CA 125 tumour markers for suspecting epithelial ovarian cancer with serous types.Methods: This research was analysis correlation and diagnostic test using cross-sectional design. This study was conducted in Dr. Zainoel Abidin Hospital, from November 2018 until April 2019. Results: There were 30 samples of patients with suspected malignant ovarian tumours. The Mann-Whitney test has been performed and the results show no relationship between the Sassone morphological index and epithelial ovarian cancer with serous type (p-value 0.627) and there was no correlation between CA 125 tumour marker and epithelial ovarian cancer with serous types (p-value 0.251). The diagnostic test was performed to examine the sensitivity and specificity for the Sassone morphological index in epithelial ovarian cancer with serous type, resulting in 60% and 28%, respectively. In this study, the sensitivity and specificity for CA 125 tumour marker in epithelial ovarian cancer with serous type were 80% and 40%, respectively. Conclusion: There was no correlation between the Sassone morphological index and CA 125 tumour marker for suspecting epithelial ovarian cancer with serous types. Keywords: CA 125 tumour marker, 0 epithelial ovarian cancer with serous types, morphological index of Sassone. Abstrak Tujuan: Untuk mengetahui adakah korelasi antara indeks morfologi Sassone dan penanda tumor CA 125 dalam memprediksi kanker ovarium epitelial tipe serous. Metode: Penelitian ini menggunakan rancangan potong lintang dengan melakukan uji korelasi dan diagnostik.Penelitian dilakukandi RSUD Dr. Zainoel abidin, dalam kurun waktu November 2018 sampai dengan April 2019.Hasil : Selama penelitian didapatkan 30 sampel penderita tumor ovarium suspek ganas. Dilakukan analisis dengan uji Mann-Whitney, didapatkan tidak terdapat hubungan antara indeks morfologi Sassone terhadap kanker ovarium epitelial tipe serous (p-value 0,627) dan tidak terdapat hubungan antara penanda tumor CA 125 terhadap kanker ovarium epitelial tipe serous (p-value 0,251). Kemudian dilakukan uji diagnostik dimana didapatkan nilai sensitivitas, spesifisitas dari indeks morfologi Sassone pada kanker ovarium epitelial tipe serous adalah 60% dan 28%. Sedangkan nilai sensitivitas dan spesifisitas penada tumor CA 125 pada kanker ovarium epitelial tipe serous pada penelitian ini didapatkan 80% dan 40%.Kesimpulan: Tidak ada hubungan antara indeks morfologi Sassone dan penanda tumor CA 125 dalam memprediksi kanker ovarium epitelial tipe serous.Kata kunci: indeks morfologi Sassone, kanker ovarium epitelial tipe serous, penanda tumor CA 125